Implementing of Inquiry Model Based on Technology to Increase Scientific Literacy and Critical Thinking - Tanryale, Masni Halimin; Astija; Kundera, I Nengah; Nurchamidah; Hamsah, Muhammad (Universitas Pendidikan Ganesha, 2025)
The low science literacy and critical thinking skills of Indonesian students as shown by the results of the Programme for International Student Assessment (PISA) are an important background for this research. This study aims to analyze the effectiveness of technology-based inquiry learning models in improving students' critical thinking skills and science literacy. The research was conducted in three madrassas using a pseudo-experimental design involving three treatment groups, namely guided inquiry, independent inquiry, and modified inquiry. The subjects of the study were madrasah students who were selected purposively. The instruments used include science literacy tests, critical thinking tests, student worksheets, and questionnaires. Data were analyzed using t-test and ANOVA to test the effectiveness between treatment groups. The results of the study show that the technology-based inquiry learning model significantly improves students' critical thinking skills and science literacy. The group with the modified inquiry model showed the most optimal results compared to the other groups. These findings suggest that the integration of technology in inquiry learning has the potential to improve students' higher-level thinking skills and science literacy. This study concludes that the application of technology-based inquiry models is very effective, especially in learning biology on complex materials such as Archaebacteria. The implication of this research is the importance of developing an inquiry-based curriculum supported by technology to support 21st century skills and improve the quality of education in Indonesia.